METB-11. HYPOXIA INDUCIBLE FACTOR 1α REPROGRAMS CHOLINE AND ETHANOLAMINE PHOSPHOLIPID METABOLISM IN MUTANT IDH1 GLIOMAS - Viswanath, Pavithra (Neuro Oncol, 2017)
Mutations in isocitrate dehydrogenase 1 (IDH1) drive tumorigenesis in low-grade gliomas and result in production of the oncometabolite 2-hydroxyglutarate (2-HG). 2-HG extensively reprograms cell metabolism, often in a manner atypical relative to wild-type IDH1 gliomas. In particular, compared to normal tissue, wild-type IDH1 gliomas are characterized by elevated levels of phosphocholine (PC) and phosphoethanolamine (PE), which are intermediates in the synthesis of the membrane phospholipids phosphatidylcholine and phosphatidylethanolamine. Mutant IDH1 gliomas, however, down-regulate PC and PE levels and we previously linked this effect to 2-HG-mediated down-regulation of choline kinase (CK) and ethanolamine kinase (EK) activity. The goal of this study was to delineate the molecular pathway by which 2-HG down-regulates this activity. Previous studies have linked hypoxia inducible factor-1α (HIF-1α) to modulation of CKα expression. Here, using two genetically-engineered models expressing mutant or wild-type IDH1 (U87-based and immortalized normal human astrocyte-based), we established that HIF-1α levels were higher in mutant IDH1 cells relative to wild-type. Mechanistically, silencing HIF-1α in mutant IDH1 cells restored CKα expression, CK activity, EK activity, PC and PE to levels observed in wild-type IDH1 cells. To further confirm our results, we treated mutant IDH1 cells with KC7F2, a pharmacological inhibitor of HIF-1α synthesis and found that it restored CKα expression, CK activity, EK activity, PC and PE to levels observed in wild-type cells. Importantly, HIF-1α silencing and KC7F2 treatment increased PC, PE, CKα expression, CK activity and EK activity in the clinically relevant BT54 patient-derived mutant IDH1 model. Finally, examination of orthotopic U87 tumors expressing mutant or wild-type IDH1 showed that PC, PE, CKα expression, CK activity and EK activity were reduced in mutant tumors relative to wild-type, an effect associated with higher HIF-1α levels in mutant tumors. Taken together, our study mechanistically links HIF-1α to the unusual down-regulation of phospholipid metabolism in mutant IDH1 gliomas.